Aplicação do Diagrama de Pejrup na Interpretação da Sedimentação e da Dinâmica do Estuário da Baía de Marajó-PA - CORRÊA, IRAN CARLOS STALLIVIERE (Pesquisas em Geociências, 2005)
<!– .p text-align: justify; –> From statistical parameters of the bottom morphology and of the application of the diagram proposed by Pejrup(1988) it was possible to characterize the dynamic and sedimentary processes that occur in the estuary of the Marajó bay. The sediments that recover the bottom of the studied area are formed by medium to very fine sands that grade to coarse to fine silt in direction to the continental shelf. The hydrodynamic of the area is dominated by the tidal and fluvial currents as well, partly due the action of winds which influence these currents. These factors associated with the estuarine circulation, are responsible for the transport, redistribution and deposition of the sediments in the study area.